Hegel's laws the legitimacy of a modern legal order - Conklin, William E. (Stanford, Calif. : Stanford University Press, 2008)
An introduction to Hegel's ideas on the nature of law. This book takes readers through different structures of legal consciousness, from the private law of property, contract, and crimes to intentionality, the family, the role of the state, and international law.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Law -- Philosophy; Law; Jurisprudence & general issues